Jantung yang Tidak Tahu Sedang Diobati: Kardiotoksisitas Anthracycline dan Urgensi Kardio-Onkologi - Raymond R. Tjandrawinata (MEDICINUS, 2026)
Anthracycline-based chemotherapy has long been a cornerstone in the management of various malignancies, however, this antineoplastic class carries a frequently under-recognized consequence in the form of subclinical cardiac injury thatdevelops long before clinical manifestations become apparent. Cardiotoxicity mediated by topoisomerase IIβ dysregulation and oxidative stress does not occur abruptly, but cumulatively, with an incidence of approximately 9% among exposed populations. The physiological paradox further complicates this phenomenon, as compensatory mechanisms may mask ongoing myocardial damage, allowing early intervention window to be frequently missed. This article argues that the traditional boundaries between oncology and cardiology are no longer sufficient, and that an integrated cardio-oncology approach, incorporating active cardiac surveillance as soon as the initiation of therapy, should be regarded as clinical necessity rather than merely a consultative option.